Pelatihan Negosiasi Bisnis sebagai Upaya Peningkatan Soft Skills Mahasiswa Program Studi Kewirausahaan - Diana Pramesti; Isti Widiharjanti; Ochi Anggreini (Universitas Pahlawan Tuanku Tambusai, 2026)
Business negotiation skills are one of the important soft skills for Entrepreneurship Study Program students to face the increasingly competitive world of work and business. However, many students still have limitations in communication, persuasion, and business negotiation skills. Therefore, business communication and negotiation training was held. The activity was held from April 15 to May 5, 2026 at the Muhammadiyah University of Bangka Belitung, involving 25 students. The implementation method included planning, preparation, implementation, and evaluation stages. The training was conducted through lectures, discussions, case studies, simulations, and group business negotiation practices. The results of the activity showed that the training was able to improve students' understanding of business negotiation concepts and strategies, interpersonal communication skills, self-confidence, teamwork, and critical thinking and problem-solving skills. The high enthusiasm of the participants during the activity also demonstrated that the applied and experience-based training method was effective in supporting the development of students' soft skills.